(untitled) (Journal of Asian Development Studies, 2025)
In this study, the chief objective was to investigate the relationship among school principals’ transformational leadership, teachers’ intrinsic motivation, job performance, and the mediating role of organizational culture. The research was descriptive and corrective. All teachers engaged at secondary schools of Mianwali district were considered the population, and a sample size of 100 teachers was selected randomly. Adapted research tools (a five-point Likert-Scale questionnaire) were used for data Collection after confirming their validity and reliability through experts’ opinions and pilot testing (α=0.84). Data analysis was done in SPSS version 26. The research revealed a moderate level of agreement between transformational leadership as practiced by secondary school principals and as perceived by teachers. This research concludes that principals’ transformational leadership, together with a supportive organizational culture, is vital for enhancing teachers’ intrinsic motivation and job performance. It was further revealed that organizational culture strengthens the connection between transformational leadership, intrinsic motivation, and teachers’ job performance. It is recommended that principals of higher secondary schools know and understand all four dimensions of transformational leadership. They can achieve this by attending training sessions and workshops on educational leadership to enhance their practices and improve teachers’ intrinsic motivation and job performance.